2013
DOI: 10.1186/1471-2202-14-60
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of different classes of glutamate receptors in the corticostriatal polysynaptic responses from striatal direct and indirect projection neurons

Abstract: BackgroundPrevious work showed differences in the polysynaptic activation of GABAergic synapses during corticostriatal suprathreshold responses in direct and indirect striatal projection neurons (dSPNs and iSPNs). Here, we now show differences and similarities in the polysynaptic activation of cortical glutamatergic synapses on the same responses. Corticostriatal contacts have been extensively studied. However, several questions remain unanswered, e.g.: what are the differences and similarities in the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 74 publications
(175 reference statements)
2
38
0
Order By: Relevance
“…Unlike AMPA receptors, localization of kainate receptors to postsynaptic densities is not ubiquitous in all neurons throughout the CNS. Prior studies have found that there is a slow synaptic current in SPNs that was not inhibited by AMPA and NMDA receptor antagonism (Chergui et al, 2000) but which was reduced by the relatively selective kainate receptor blocker ACET (Vizcarra-Chacon et al, 2013). We confirmed that kainate receptors contribute to corticostriatal synaptic transmission by mediating a small amplitude GYKI53655-resistant current that was partially blocked by the non-selective AMPA/kainate receptor antagonist CNQX (n = 20 WT, n = 3 5ko) (Figure 3B & C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike AMPA receptors, localization of kainate receptors to postsynaptic densities is not ubiquitous in all neurons throughout the CNS. Prior studies have found that there is a slow synaptic current in SPNs that was not inhibited by AMPA and NMDA receptor antagonism (Chergui et al, 2000) but which was reduced by the relatively selective kainate receptor blocker ACET (Vizcarra-Chacon et al, 2013). We confirmed that kainate receptors contribute to corticostriatal synaptic transmission by mediating a small amplitude GYKI53655-resistant current that was partially blocked by the non-selective AMPA/kainate receptor antagonist CNQX (n = 20 WT, n = 3 5ko) (Figure 3B & C).…”
Section: Resultsmentioning
confidence: 99%
“…The mice also had multiple alterations in motor behaviors with a classic hind limb clasping phenotype, impairments in the accelerating rotarod, and alterations in gait. Kainate receptors are expressed in striatal neurons, yet little is known about their contribution to synaptic transmission (Chergui et al, 2000; Vizcarra-Chacon et al, 2013). We found that corticostriatal synaptic transmission in the dorsal striatum was impaired, with changes in the NMDA:AMPA ratio, as well as reductions in the field potential response and lower mEPSC frequencies both suggesting the existence of fewer excitatory synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Near synaptic sites of SPNs, NMDA, Ca V 1, Ca V 2.3, and Ca V 3 channels become a main source of Ca 2+ (Galarraga et al, 1997; Carter and Sabatini, 2004; Higley and Sabatini, 2008; Flores-Barrera et al, 2011). Because Ca 2+ -activated K + -channels could be present in the synaptic regions of dendrites (Ngo-Anh et al, 2005; Gu et al, 2008; Benhassine and Berger, 2009; Wynne et al, 2009; Faber, 2010; Grewe et al, 2010; Allen et al, 2011; Hosy et al, 2011; Tonini et al, 2013, e.g., Womack et al, 2004), one question to ask is whether Ca 2+ -activated K + currents are involved in dendritic synaptic integration and the repolarization of polysynaptic corticostriatal responses (Vizcarra-Chacon et al, 2013), given that Ca 2+ sources could be different than in the soma. Different sources of Ca 2+ to activate Ca 2+ -dependent K + -currents in the dendrites and the soma-axon hillock regions could imply that synaptic inputs and the generation of action potentials may be regulated differentially.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that cholinergic neurons respond with a slightly briefer latency than the responses of SPNs [1, 24]. In addition, continuous firing of cholinergic interneurons maintains a tonic level of ACh in the striatum [7, 24, 45], muscarinic M 1 receptors are expressed in all SPNs, and K V 7 channels have been shown to compose a minor but functionally important part of the intrinsic voltage gated currents that are present in all SPNs [34].…”
Section: Resultsmentioning
confidence: 99%